The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/antiox10111741
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Salivary Immuno-Biochemical Markers and HbA1c in Type 2 Diabetes Subjects before and after Dental Extraction

Abstract: Dental extraction can trigger certain sequences of complex processes that involve both hard (alveolar bone) and soft tissue (periodontal ligament, gingiva) remodeling. Type 2 diabetes is a serious risk factor for many oral pathologies, both in terms of progression and severity, but also regarding subsequent rehabilitation possibilities. The aim of this study was to establish whether certain molecules: osteoprotegerin (OPG), kappa B nuclear factor receptor activator ligand (RANKL), hepatocyte growth factor (HGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In general, stress is always accompanied by oxidant stress [ 36 ]. Oxidant stress is an imbalance caused by excess free radicals and the body’s inability to counteract the damage they cause, which is a causative factor in various pathologies, such as cancer, diabetes, neurological diseases and liver disease [ 37 , 38 , 39 , 40 ]. In our present study, Western blot, qRT-PCR and immunohistochemistry analysis show that cold stress-induced Nrf2, HO-1, NQO1, GCLC and GCLM distinctly increased.…”
Section: Discussionmentioning
confidence: 99%
“…In general, stress is always accompanied by oxidant stress [ 36 ]. Oxidant stress is an imbalance caused by excess free radicals and the body’s inability to counteract the damage they cause, which is a causative factor in various pathologies, such as cancer, diabetes, neurological diseases and liver disease [ 37 , 38 , 39 , 40 ]. In our present study, Western blot, qRT-PCR and immunohistochemistry analysis show that cold stress-induced Nrf2, HO-1, NQO1, GCLC and GCLM distinctly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that the immuno‐biochemical markers can be used as a predictor of diabetes and their complications 28,29 . If the results be confirmed by comprehensive studies, the assessment of salivary samples, especially in high‐risk persons can be a non‐invasive alternative method for beneficial screening and a good substitute for traditional techniques, such as serum collection.…”
Section: Discussionmentioning
confidence: 99%
“…An important role in the evolution of many inflammatory diseases is attributed to reactive oxygen species (ROS), and changes in the activity of antioxidants in periodontal disease are influenced by systemic conditions. Furthermore, oxidative status markers and proinflammatory biomarkers are modified in the saliva of diabetic patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%